THE INFLUENCE OF INTERFACE QUALITY, INFORMATION QUALITY AND CUSTOMER SERVICE ON CUSTOMER SATISFACTION AT ONLINE SHOP IN MANADO AT SAM RATULANGI UNIVERSITY STUDENTS - Lumataw, Yurike V.; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: In today's competitive business environment marketing managers are more influenced from customerexpectation and meeting the demand for customer satisfaction is very important for them. Every organization must definecustomer satisfaction regarding their market. This study objectives are to influences of interface quality, informationquality and customer service on consumer satisfaction at online shop in Manado. This study is conducted in Faculty ofEconomics and Business Sam Ratulangi University at Manado. This research finding that the interface quality, informationquality and customer service has a positive and significant influence on customer satisfaction. Based on the results ofhypothesis testing found that interface quality, information quality, and customer service has significant and positiveimpact partially on customer satisfaction of online shop in Manado. Suggestions: for online stores in Manado, thesefindings must be taken into consideration in making decisions to increase the satisfaction of consumers who buy at onlinestores, especially for milineal consumers or the younger generation. This is because this consumer is one of the biggestconsumers who shop online and start buying online at a young age. This is also supported by money obtained from parentsor income derived from doing business online or other businesses carried out by millennial generations.Keywords: interface quality, information quality, customer service, customer satisfaction, online shop, university students,Manado